Exploration of genetic basis of differential immune response to CSF vaccination in desi (indigenous) piglets using RNA-Seq approach - SAH, VAISHALI; KUMAR, AMIT; KUMAR, RAVI; PATHAK, SHALU KUMARI; WANI, SAJAD AHMAD; SAHU, AMIT RANJAN; UPMANYU, VIKRAMADITYA; SAHOO, NIHAR RANJAN; BHUSHAN, BHARAT (The Indian Journal of Animal Sciences, 2017)
In the present study, the transcriptome profiling of peripheral blood mononuclear cells (PBMCs) of indigenous piglets against classical swine fever (CSF) vaccination was performed for elucidating the genetic basis of their differential humoral immunity. Piglets were vaccinated with lapinised strain of CSF virus (CSFV) followed by measurement of humoral immune response using c-ELISA at 28th day post vaccination (28dpv). The RNA sequencing data was analysed using established pipeline to determine set of differentially expressed genes (DEGs) in high responder as compared to low responder piglet. The differentially expressed important immune molecules were involved in regulating important pathways including antigen processing and presentation, T cell receptor signalling, B cell development, activation and signaling genes. The genes with differential expression also included TLR 3, 6, 7, 8, 9, and antiviral molecules such as MX, and ISG (Interferon stimulated genes) family members. The proteinprotein interaction of the immune genes was extracted for network representation. Most of the immune genes involved showed upregulation except the genes for antigen processing and presentation and T cell receptor signaling that were downregulated in the high responder. The immunologically important genes namely IFIT1, IFIT5, TAPBP, and TLR7 were validated using qRT-PCT and were observed to be in concordance with the RNA Seq results.